Penerapan Sistem Pertanggungjawaban Pidana bagi Lembaga Perbankan ditinjau dari Teori-Teori Sistem Pertanggungjawaban Pidana Korporasi - Kristian Kristian (Fakultas Hukum, Universitas Islam Bandung, 2019)
The economy of the modern society is closely related or even inseparable with the world of banking. It is due to the fact that the main function of banking institutions is basically as an intermediary. However, the fact that the existence of banking institutions is as a corporation does not always have a positive impact. It can also impact negatively in the sense that the banking institution as a corporation becomes a perpetrator of criminal acts or conducts various criminal acts harmful to the public but untouchable by law.The results show that banking institutions (banks) can be categorized as corporations according to the criminal law. Consequently, as a legal subject, the bank is supposedly liable to commit a criminal offense and may be held accountable for criminal acts. The corporate criminal liability system has been legitimized and justified by several doctrines or theories: identification theory, strict liability theory, vicarious liability doctrine, the corporate culture model or company culture theory, doctrine of aggregation, and reactive corporate fault. If it is related to the subject matter, the corporate criminal liability system, as legitimized and justified by the various theories, can be applied to banking institutions. Hence, according to such theories or doctrines, the bank is deemed able to commit criminal acts and bear criminal liability. In addition, the arrangement and application of corporate criminal liability systems for banking institutions may also be justified by several fundamental or principal reasons.However, it is unfortunate that the system of criminal liability for banking institutions as a corporation is not yet applicable. This is because the current banking law is still dominated by the principle of